One good story, that one : stories - King, Thomas, 1943- (University of Minnesota Press, 2013)
One Good Story, That One is a collection steeped in native oral tradition and shot through with Thomas King's special brand of wit and comic imagination. These highly acclaimed stories conjure up Native and Judeo-Christian myths, present-day pop culture, and literature while mixing in just the right amount of perception and experience.